2020
DOI: 10.1016/j.jclepro.2020.123848
|View full text |Cite
|
Sign up to set email alerts
|

Coupling coordination between carbon emissions and the eco-environment in China

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 69 publications
(67 reference statements)
1
35
0
Order By: Relevance
“…Liu et al [ 11 ] also used the above methods to analyze the CCD between Nansi Lake catchment’s social economy and the water environment. Chen et al [ 12 ] studied the CCD of China’s carbon emissions and the ecological environment from 2009 to 2015 based on the CCD model and found that the two barely reached a dynamic balance. Based on remote sensing data, Ariken et al [ 13 ] analyzed the relationship between urbanization and eco-environment in China’s typical arid area of Yanqin Basin using the CCD model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al [ 11 ] also used the above methods to analyze the CCD between Nansi Lake catchment’s social economy and the water environment. Chen et al [ 12 ] studied the CCD of China’s carbon emissions and the ecological environment from 2009 to 2015 based on the CCD model and found that the two barely reached a dynamic balance. Based on remote sensing data, Ariken et al [ 13 ] analyzed the relationship between urbanization and eco-environment in China’s typical arid area of Yanqin Basin using the CCD model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies argue that renewable energy consumption enhances financial and economic development (Kemmler and Spreng 2007 ; Vasylieva et al 2019 ), whereas other extant literature found that FD spurs REC (Apergis et al 2020 ; Ji and Zhang 2019 ; Qamruzzaman and Jianguo 2020 ). Since developed countries work on zero-carbon emission plan (for example see Shahbaz et al 2020 ), emerging economies still account for a significant portion of GHG emissions worldwide (Apergis and Garzón 2020 ; Chen et al 2020 ). Therefore, we intend to highlight the relationship between FD and REC in emerging countries.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, the coastal regions (Jiangsu and Shanghai) and Hubei had better performances mainly because of the adequate budget for both higher education and science popularization, large amount of output in higher education, large scale of science popularization venues, and high qualified stakeholders (such as teachers, students, personnel, and visitors) of the two systems. Such spatial differences appear in former studies; for instance, spatial differences exist when analyzing the coupling coordination relations between carbon emission and eco-environment [ 67 ]. (2) Though there were gaps compared with other places, the western regions (especially Guizhou) were accelerating their coordinated growth performances and were gradually reducing the gap.…”
Section: Resultsmentioning
confidence: 99%